Hubungan Manajemen Laba Setelah IPO dan Return Saham dengan Kecerdasan Investor sebagai Variabel Pemoderasi - Joni - Joni . (Jurnal Akuntansi, 2008)
The major purpose of this study is to investigate the association between earnings management after IPO and stock returns with investors sophistication as a moderating variable. Institutional ownership is used to proxy investors sophistication.The JSX (Jakarta Stock Exchange) listed companies and issuers of IPO from 1990 to 2002 period is used as samples. The companies which institutional ownership >/ 40% consist of 75 IPOs. Earnings management was detected with Instrumental Variable Approach (Kang and Sivaramakrishnan, 1995).This study provides an evidence that issuers report unusually high earnings management around 1Po (two years before and five years afier IPO. Issuers used mean reversing strategy in two years before IPO period (income decreasing) for preparing earnings management in the next period (income increasing). Furthermore, this study documents there is no association between earnings management and stock returns with investorssophistication as moderating variable.Keywords: IPO, Earnings Management, Instrumental Variable Approach, Stock Returns, Investors Sophistication.